Die Organisation von Zwangs-Arbeitseinsatz in den eingegliederten Gebieten in der ersten Phase des Krieges (am Beispiel Oberschlesiens) [The organisation of forced labour in the incorporated areas in the first phase of the war (using the example of Upper Silesia)] - Sroka, Irena (Studia Historiae Oeconomicae, 1979)
This article examines the organization and implementation of forced labor deployment in the Katowice administrative district (Upper Silesia) during the initial phase of the German occupation following the invasion of Poland in September 1939. The region, rich in industry and natural resources, was quickly incorporated into the Reich, with its economic assets particularly labor potential – fully mobilized in support of the Third Reich’s war economy. The aim of the study is to analyze the administrative, legal, and practical mechanisms used by Nazi authorities to forcibly integrate the Polish population into the labor process – both locally and through deportations to the Reich. The study is based on archival materials, particularly from the WAPK (Voivodeship Archives in Katowice), and draws on statistical data as well as concrete examples from labor offices and industrial centers. Findings show that as early as September 1939, systematic registration of all able-bodied individuals began – including women, youth, and the elderly. Within a few months, tens of thousands of Poles were deported to the German Reich for forced labor, often under threat of violence or through economic coercion – primarily to work in agriculture and heavy industry. Simultaneously, local labor was recruited for mining and metallurgy, with employment decisions often made along political and ethnic lines. By 1941, over 58,000 individuals from the Katowice district had been transported for labor outside the region. Forced labor was a central instrument of German occupation policy, aimed not only at exploiting the Polish population economically but also at supporting long-term plans for the Germanization of the region.